Malaria in injection drug abusers in Vietnam. - Chau, T; Mai, N; Phu, N; Luxemburger, C; Chuong, L; Loc, P; Trang, T; Vinh, H; Cuong, B; Waller, D; Sinh, D; Day, N; et al. (2002)
A prospective case-control study was conducted in a referral hospital in Ho Chi Minh City, Vietnam, to compare the clinical and laboratory features and outcome of severe falciparum malaria in injection drug abusers (IDAs) with those of patients who had acquired malaria by mosquito bite. From 1991 to 1996, 70 IDAs were admitted to the hospital, of whom at least 32 had acquired malaria by needle sharing. Although IDAs were more likely than control patients with severe malaria to be malnourished and to have coincident hepatitis B, hepatitis C, and human immunodeficiency virus infections, the overall rates of mortality, complications, and recovery were similar in the 2 groups. The route of malaria acquisition did not affect the outcome of severe malaria. The management of severe malaria in IDAs is similar to that for other patients.